Comparative Study of Model Reference Adaptive Control (MRAC) and PID Controller for Regulation Temperature of Steam Distillation System - Amron, Aqilaa; A. Jalil, Mohd Hafiz; Rohaiza Hamdan; Salehin, Nur Suhadah; Rafidah Ngadengon (Evolution in Electrical and Electronic Engineering, 2021)
Steam distillation is an important part of essential oil extraction. However, controlling the temperature at the correct temperature has proven difficult for the industry. Furthermore, if the extraction process is conducted to excessive heat, the essential oil quality will weaken. Therefore, the focus of this research to evaluate the performance of Model Reference Adaptive Control (MRAC) in regulating steam distillation temperature. The results reveal that the MRAC without integral outperforms the PID controller in preventing overshoot and providing a 40 % faster settling time when compared to the PID controller. This signifies that the MRAC is a controller that might be used to improve the steam distillation process for future work of steam distillation development.